Security, privacy, and applied cryptography engineering : 7th International Conference, SPACE 2017, Goa, India, December 13-17, 2017, Proceedings /: 7th International Conference, SPACE 2017, Goa, India, December 13-17, 2017, Proceedings. (2017) - Unknown
No abstract available